PENGARUH EDUKASI GIZI DENGAN METODE FOCUS GROUP DISCUSSION TERHADAP PENGETAHUAN TENTANG DIET HIPERTENSI PADA LANSIA DI DESA JOMBATAN KABUPATEN JOMBANG - Gilang Akbar Shobirin (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: The prevalence of elderly hypertension in Indonesia is increasing, it can be caused by several factors as high salt consumption, poor living habits, and lack of knowledge about hypertension diets. Increasing knowledge about the hypertension diet or low salt foods can be done by providing education in the form of counseling. Objective: This study aimed to influence the nutrition education of focus group discussion methods on changes in knowledge, about hypertension diet in elderly with hypertension in Jombatan, Jombang Regency. Methods: This type of research used in this study is Quasy experimental research (quasi-experimental) with one group pretest-posttest design. The number of samples in this study were 30 elderly (≥ 60 years old) in Jombatan, Jombang Regency. When this research was conducted in Desembern2022. The independent variable is nutrition education and the dependent variable is knowledge of the hypertension diet. Knowledge data obtained by structured interviews using a questionnaire. The statistical test used is paired t-test. Results: The results of the blood pressure of respondents as much as 86.6% were classified as hypertension one, knowledge data had increased after being given nutrition education (good category of 66.6%). Conclusion: The conclusion from this study is that there is an educational effect of the Focus Group Discussion (FGD) method on knowledge of the hypertension diet (p-value = 0.001).